Presidential Threshold: Konsep Open Legal Policy Oleh Mahkamah Konstitusi 2017-2022 - Gazali, Mardania; Kamis, Margarito; Rumkel, Nam (Universitas Widya Gama Malang, 2024)
This study aims to analyze the constitutional interpretation method used by constitutional judges in judicial review the presidential threshold as an open legal policy for 2017-2022 and to offer an ius constituendum to use the open legal policy by the Constitutional Court in the future. The type of research used is normative legal research, namely research conducted by examining legal materials consisting of primary legal materials, secondary legal materials, and tertiary legal materials using a case approach and a conceptual approach. The data collection technique used in this research is using a literature study and the data will be analyzed using the descriptive analysis method. The research found that the Constitutional Court in judicial review the presidential threshold from 2017 to 2022 all used structural , thus interpreting the presidential threshold norm and its touchstone as an open legal policy. But unfortunately, the interpretation made by the constitutional judge is incorrect and has changed the original meaning of the formation of Article 6A paragraph (2) of the NRI Constitution of 1945. The original intent of the establishment of Article 6A paragraph (2) of the NRI Constitution of 1945 was to place political parties or a combination of political parties as a path to propose candidates for President and Vice President because the framers of the amendment did not want an independent candidate. Therefore, the interpretation of constitutional judges declaring the presidential threshold and Article 6A paragraph (2) of the NRI Constitution of 1945 as open legal policy is wrong because the article is clear. In the future, constitutional judges can divide open legal policy into two forms, namely absolute and relative, both of which can be reviewing, and constitutional judges can expand the touchstone of the Basic Law which not only includes article norms but also includes the Preamble in which Pancasila and cancels the formulation of presidential threshold norms to 0% in order to provide justice to justice seekers.